INDONESIAN QUALIFICATION FRAMEWORKS (IQF): HOLISTIC VIEW ON POTENTIAL BENEFITS AND FURTHER ISSUES - Rohmah, Galuh Nur (Jurnal Bahasa Lingua Scientia, 2014)
This paper aims to discuss Indonesian Qualification Frameworks (IQFs) holistically. Today, we are being exposed to the discussions on IQFs through many socialization programs and government publications. As education practitioners, we have to be familiar with universal concepts of National Qualifications Framework (NQF) which most pioneers of NQF hold. It is not enough only having that, moreover, this paper presents other essential points about NQF and, specifically for Indonesian context, those are the potential benefits, the reasons of formulating IQFs, NQFs across countries, and further issues. I realize that this paper has not successfully contextualized into ELT as IQFs has recently been developed. However, this paper is significant engagement to IQFs for successful implementation.